Lack of Connexins 40 and 45 Reduces Local and Conducted Vasoconstrictor Responses in the Murine Afferent Arterioles - Møller, Sophie; Jacobsen, Jens Christian Brings; Holstein-Rathlou, Niels-Henrik; Sorensen, Charlotte M. (Frontiers in Physiology, 2020)
The juxtaglomerular apparatus (JGA) is an essential structure in the regulation of renal function. The JGA embodies two major functions: tubuloglomerular feedback (TGF) and renin secretion. TGF is one of the mechanisms mediating renal autoregulation. It is initiated by an increase in tubular NaCl concentration at the macula densa cells. This induces a local afferent arteriolar vasoconstriction and a conducted response that can be measured several 100 μm upstream from the juxtaglomerular segment. This spread of the vasomotor response into the surrounding vasculature likely plays a key role in renal autoregulation, and it requires the presence of gap junctions, intercellular pores based on connexin (Cx) proteins. Several Cx isoforms are expressed in the JGA and in the arteriolar wall. Disruption of this communication pathway is associated with reduced TGF, dysregulation of renin secretion, and hypertension. We examine if the absence of Cx40 or Cx45, expressed in the endothelial and vascular smooth muscle cells respectively, attenuates afferent arteriolar local and conducted vasoconstriction. Afferent arterioles from wildtype and Cx-deficient mice (Cx40 and Cx45) were studied using the isolated perfused juxtamedullary nephron preparation. Vasoconstriction was induced via electrical pulse stimulation at the glomerular entrance. Inner afferent arteriolar diameter was measured locally and upstream to evaluate conducted vasoconstriction. Electrical stimulation induced local vasoconstriction in all groups. The local vasoconstriction was significantly smaller when Cx40 was absent. The vasoconstriction decreased in magnitude with increasing distance from the stimulation site. In both Cx40 and Cx45 deficient mice, the vasoconstriction conducted a shorter distance along the vessel compared to wild-type mice. In Cx40 deficient arterioles, this may be caused by a smaller local vasoconstriction. Collectively, these findings imply that Cx40 and Cx45 are central for normal vascular reactivity and, therefore, likely play a key role in TGF-induced regulation of afferent arteriolar resistance.